2015
DOI: 10.1177/0284185115574156
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for conventional MRI and MR diffusion-weighted imaging for distinction of skull base chordoma and chondrosarcoma?

Abstract: An off-midline growth pattern can differentiate chondrosarcoma from chordoma on cMRI in a majority of patients. Additional DWI is a promising tool for the differentiation of these skull base tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
0
33
2
Order By: Relevance
“…2 DWI could potentially be used to distinguish chordoma from chondrosarcoma because the ADC values for chordoma are lower than those for chondrosarcoma. 3,4 Moreover, the ADC values are lower in aggressive chordomas than in classic chordomas, suggesting that ADC may be useful for classifying chordomas into subcategories according to aggressiveness. 4 Hanna et al 5 suggested that a low T2 component in chordoma represented aggressive chordoma.…”
mentioning
confidence: 99%
“…2 DWI could potentially be used to distinguish chordoma from chondrosarcoma because the ADC values for chordoma are lower than those for chondrosarcoma. 3,4 Moreover, the ADC values are lower in aggressive chordomas than in classic chordomas, suggesting that ADC may be useful for classifying chordomas into subcategories according to aggressiveness. 4 Hanna et al 5 suggested that a low T2 component in chordoma represented aggressive chordoma.…”
mentioning
confidence: 99%
“…The tumor borders are clear, and intratumoral calcification is a no-signal area. After the enhanced scan, the tumor was mildly heterogeneous and the calcified area was not enhanced [14]. However, ChSa is not easy to distinguish from chordoma in imaging [15].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor borders are clear, and intratumoral calci cation is a no-signal area. After the enhanced scan, the tumor was mildly heterogeneous and the calci ed area was not enhanced [14]. However, ChSa is not easy to distinguish from chordoma in imaging [15].…”
Section: Discussionmentioning
confidence: 99%